Pengembangan Sediaan Dengan Pelepasan Dimodifikasi Mengandung Furosemid Sebagai Model Zat Aktif Menggunakan Sistem Mukoadhesif - Sutriyo, Sutriyo; Rachmat, Hasan; Rosalina, Mita (UI Scholars Hub, 2008)
Drug bioavailability is one of the parameter which is used to evaluate the effectiveness of pharmaceutical dosage form. Rate of dissolution and drug residence time in gas-trointestinal tract is a factor which can influence the bioavailability. Solid dispersion and mucoadhesive drug delivery system is one of the method which can be used to solve the problem concerning the rate of dissolution and residence time in gastrointes-tinal tract. In this research mucoadhesive microgranule had been made with furo-semide as a drug model and Carbopol 934P® as a mucoadhesive polimer. The mucoadhesive microgranules resulted from this investigation has a particle size range of 425-850 µm, and was evaluated by type 1, 100 rpm speed and phosphate buffer pH 5.8 dissolution test and by wash off test. Furosemide was made in solid dispersion with polyvinylpyrrolidone (PVP K30®) with weight ratio of 1:7 using solubility method. The results showed increasing the dissolution rate of furosemide in solid dispersion compared to pure furosemide. Increasing the concentration of Carbopol 934P® in microgranule will cause inhibition of drug release and increasing the amount of microgranule sticked to gastric and intestinal mucous.